Zircon dating of the basalt and felsic dyke in Haveri, SW Finland - Kara Jaakko; Väisänen Markku; O'Brien Hugh (Geological Society of Finland, 2025)
The E-MORB type Haveri basalt differs from the volcanic arc type rocks in the Tampere
belt showing no subduction signature. It is considered to have formed in a marginal
basin prior to the volcanic arc. We present here zircon U-Pb dating on two samples. The
basalt and the felsic dyke yielded 207Pb/206Pb ages of 1902 ± 5 Ma and 1891 ± 2 Ma,
respectively, interpreted as crystallisation ages. The basalt also contains older 1.98 Ga
grains while the felsic dyke contains older 1.92 Ga, 1.94 Ga, 1.98 Ga and 2.0 Ga grains,
which are inferred as inherited. The age dating of E-MORB type basalts can be used to
identify the extensional episodes of the accretionary Svecofennian orogeny.